Calculation Method of Bonding Section of Joint Surface of Dangerous Rock Mass Based on Amplitude Ratio - Qingbo Li; Hongfei Wang; Mowen Xie; Weinan Liu (Shock and Vibration)
In this study, through an analysis of vibration response characteristics of joint surface stiffness on dangerous rock mass, the relationship formula between amplitude ratio of the dangerous rock mass to the bedrock and the length of the bonding section of the joint surface is determined. The stability of the rock mass can be evaluated by combining the formula with the existing rock-mass limit equilibrium theory. This study proposes the existence of a resonance bonding length for the dangerous rock mass. When the length of the bonding section reaches the resonance bonding length, the dangerous rock mass has the largest response to the bedrock vibration. The study found that when the length of the bonding section of the dangerous rock mass is longer than the resonance bonding length, the amplitude ratio increases with the decrease of the bonding section and increases with the increase of the vibration frequency of the bedrock. When the length of the bonding section of the dangerous rock body is shorter than the resonance bonding length, the amplitude ratio decreases with the decrease of the bonding section and decreases with the increase of the vibration frequency of the bedrock. Indoor experiments were conducted by collecting the vibration time-history curves of rock blocks and stone piers and performing analysis and calculation, which proved the accuracy of the analytical results. Through the amplitude ratio of the dangerous rock mass and the bedrock, the bonding length can be calculated. This method can improve the calculation accuracy of the stability coefficient K of the dangerous rock mass.